1997
DOI: 10.1038/387292a0
|View full text |Cite
|
Sign up to set email alerts
|

The role of RhoA in tissue polarity and Frizzled signalling

Abstract: The tissue polarity genes of Drosophila are required for correct establishment of planar polarity in epidermal structures, which in the eye is shown in the mirror-image symmetric arrangement of ommatidia relative to the dorsoventral midline. Mutations in the genes frizzled (fz), dishevelled (dsh) and prickle-spiny-legs (pk-sple) result in the loss of this mirror-image symmetry. fz encodes a serpentine receptor-like transmembrane protein required for reception and transmission of a polarity signal. Little else … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
493
0
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 519 publications
(509 citation statements)
references
References 27 publications
14
493
0
2
Order By: Relevance
“…Alternatively, JNK signaling may not be required for photoreceptor di erentiation per se, but for a distinct developmental event such as rotation of the eye facets. Indeed, genetic epistasis has placed bsk, hep, rhoA and dishevelled (dsh) in a pathway downstream of the Frizzled (Fz) serpentine receptor in generating proper tissue polarity based on dominant suppression, by mutations in these genes, of Fz-or dsh-induced ommatidial rotation defects (Boutros et al, 1998;Strutt et al, 1997). The connection between dsh and bsk is further supported by experiments in tissue culture cells which revealed that transfected dsh is capable of stimulating JNK activity (Boutros et al, 1998).…”
Section: Jnk Signaling In Tissue Polaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, JNK signaling may not be required for photoreceptor di erentiation per se, but for a distinct developmental event such as rotation of the eye facets. Indeed, genetic epistasis has placed bsk, hep, rhoA and dishevelled (dsh) in a pathway downstream of the Frizzled (Fz) serpentine receptor in generating proper tissue polarity based on dominant suppression, by mutations in these genes, of Fz-or dsh-induced ommatidial rotation defects (Boutros et al, 1998;Strutt et al, 1997). The connection between dsh and bsk is further supported by experiments in tissue culture cells which revealed that transfected dsh is capable of stimulating JNK activity (Boutros et al, 1998).…”
Section: Jnk Signaling In Tissue Polaritymentioning
confidence: 99%
“…In this way, more than two dozen genes have been characterized that when mutant either zygotically, or maternally, or both, give rise to varying degrees of open cuticles. Most of the genes fall into several groups based on the proposed functions of each gene product ( (Harden et al, 1996Strutt et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…JNK is required for tissue polarity in flies and for CE movements in frogs (Boutros et al, 1998;Strutt et al, 1997;Paricio et al, 1999;Fanto et al, 2000;Weber et al, 2000;Yamanaka et al, 2002) and is regulated by several core PCP genes (Veeman et al, 2003b). In particular, Rho GTPases, including RhoA, Rac1, and Cdc42, play essential roles in JNK regulation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Rho GTPases, including RhoA, Rac1, and Cdc42, play essential roles in JNK regulation. In Drosophila, RhoA and Rac1 but not Cdc42 genetically interact with JNK in PCP pathway (Strutt et al, 1997;Boutros et al, 1998;Fanto et al, 2000;Weber et al, 2000). In HEK293T cell, only Rac1 mediates JNK activation by Dsh (Habas et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments reported here using mutants, specific antibodies to the cross-links, and drugs that affect actin assembly and/or phosphorylation help us understand more about the control of bundle formation in vivo. Once we know what happens in a cell, we can begin to dissect how individual components are regulated, a regulation that ultimately involves cascades orchestrated by cdc42 (Eaton et al 1996) and Ras (Harden et al 1995; Eaton et al 1996), Rho (Strutt et al 1997; Hacker and Perrimon 1998), Raf (Tsuda et al 1993), and Ral (Sawamoto et al 1999). In addition, our results give us clues as to what regulates other features of the actin bundles, such as their shape.…”
Section: Introductionmentioning
confidence: 99%